Cracking in autoclaved aerated concrete: Experimental investigation and XFEM modeling. (January 2015) - Ferretti, D.; Michelini, E.; Rosati, G.
Abstract: The paper aims to investigate and model cracking development in beams and deep-beams made of autoclaved aerated concrete (AAC). Fracture mechanics of AAC has been first studied by performing three-point bending tests on beams, similar to those commonly used for ordinary concrete elements. In some of these tests, crack growth has been also monitored by using ESPI laser technique. In this way, it has been possible to calibrate the main parameters of a proper cohesive law by means of extended finite element inverse analysis. Subsequently, cracking tests have been also performed on deep-beams, whose behavior is more representative of full scale walls. To validate the proposed cohesive law, deep-beam experimental behavior has been finally simulated through XFEM.